1989
DOI: 10.1111/j.1439-037x.1989.tb00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Growth and Chlorophyll Content of Oilseed Rape (Brassica napus L.) as Influenced by Nitrogen Supply

Abstract: An experiment was conducted using a greenhouse hydroponics system to investigate the influence of N nutrition on leaf growth and chlorophyll content in oilseed rape (Brassica napus L.) during both vegetative and generative growth. Plants were treated continuously with one of three levels of N supply (30, 100 or 170ppm N). Leaf expansion in terms of lamina area of individual leaves and leaf area per plant, and chlorophyll content of leaves during both growth phases were increased significantly by N supply up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…It has been shown that the principal effects of increasing N status in Brassica napus include an increase in leaf number and area (Allen and Morgan, 1972;Gammelvind et al, 1996;Leleu et al, 2000;Svecnjak and Rengel, 2006;Wright et al, 1988;), leaf chlorophyll content (Ogunlela et al, 1989), and pod number and area (Allen and Morgan, 1972;Gammelvind et al, 1996;Hocking et al, 1997;Leleu et al, 2000;Taylor et al, 1991). Because crop N uptake mostly occurs prior to pod development, the yield response of oilseed rape to N fertilization will depend, in part, on the capacity of the crop to remobilize N from senescing vegetative organs and to transfer this N to developing seeds.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that the principal effects of increasing N status in Brassica napus include an increase in leaf number and area (Allen and Morgan, 1972;Gammelvind et al, 1996;Leleu et al, 2000;Svecnjak and Rengel, 2006;Wright et al, 1988;), leaf chlorophyll content (Ogunlela et al, 1989), and pod number and area (Allen and Morgan, 1972;Gammelvind et al, 1996;Hocking et al, 1997;Leleu et al, 2000;Taylor et al, 1991). Because crop N uptake mostly occurs prior to pod development, the yield response of oilseed rape to N fertilization will depend, in part, on the capacity of the crop to remobilize N from senescing vegetative organs and to transfer this N to developing seeds.…”
Section: Introductionmentioning
confidence: 97%
“…2001). All vegetative plant parts, especially leaves, increase their weight and chlorophyll content with increasing soil and fertilizer N supply (Ogunlela et al. 1989, Gammelvind et al.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors such as leaf mass per area (LMA) or partitioning of dry matter to stem may also affect pNUE (Brown and Wilson 1983). At the biochemical level, high N supply increased leaf protein and chlorophyll (Chl) contents and content of several enzymes involved in CO 2 fixation (Wong 1979, Hesketh et al 1981, Girardin et al 1985, Evans 1989, Ogunella et al 1989.…”
mentioning
confidence: 99%